PELATIHAN DAN PENDAMPINGAN MANAJEMEN PETERNAKAN ITIK DALAM RANGKA MENINGKATKAN PENDAPATAN PETERNAK DAN POPULASI PLASMA NUTFAH TERNAK LOKAL DI KELOMPOK TERNAK ITIK KEBERSAMAAN (K-TIK) DUSUN CIHERANG KIDUL (BOGOR) - Khuluq, Mohammad Aldi Khusnul; Noveanto, Ivan; Rahmadani, Fransiska; Rosa, Rahayu Asmadini; Aini, Fitria Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Duck farming business prospects are very promising especially in Bogor and surrounding areas . It is because the demand for meat and duck eggs are quite large and and business development is still slightly in the area of Bogor. Kelompok Ternak Itik Keberlanjutan ( KTIK ) is one of the groups of cattle that can catch these opportunities, however, due to limited knowledge of farm management and support facilities make this difficult group to fulfill market need. The PKM program using case study methods, training, collaboration, mentoring and evaluation for 5 months. Usefulness of the program to create new job opportunities and improving the lives of farmers, and stimulate students to think of creative, innovative, and dynamic. Results obtained from the PKM program is increasing basic knowledge about management duck farming which characterized by decreasing the percentage of answers does not know and incresing answer know and very aware. Income of the group increased from Rp Rp 775.000/month to 2.857.600/month result of the average sales strategies. This will assist in the smooth and KTIK progress in the future in an effort of the duck. This program is in collaboration with Himpunan Mahasiswa Nutrisi dan Makanan Ternak (HIMASITER ) to conduct training and supervision during the agreed cooperation agreement.